Hydroxyurea-Increased Fetal Hemoglobin Is Associated with Less Organ Damage and Longer Survival in Adults with Sickle Cell Anemia - Fitzhugh, Courtney D.; Hsieh, Matthew M.; Allen, Darlene; Coles, Wynona A.; Seamon, Cassie; Ring, Michael; Zhao, Xiongce; Minniti, Caterina P.; Rodgers, Griffin P.; Schechter, Alan N.; Tisdale, John F.; Taylor, James G. (PloS one, 2015)
Adults with sickle cell anemia (HbSS) are inconsistently treated with hydroxyurea. We retrospectively evaluated the effects of elevating fetal hemoglobin with hydroxyurea on organ damage and survival in patients enrolled in our screening study between 2001 and 2010. An electronic medical record facilitated development of a database for comparison of study parameters based on hydroxyurea exposure and dose. This study is registered with ClinicalTrials.gov, number NCT00011648. Three hundred eighty-three adults with homozygous sickle cell disease were analyzed with 59 deaths during study follow-up. Cox regression analysis revealed deceased subjects had more hepatic dysfunction (elevated alkaline phosphatase, Hazard Ratio = 1.005, 95% CI 1.003-1.006, p<0.0.0001), kidney dysfunction (elevated creatinine, Hazard Ratio = 1.13, 95% CI 1.00-1.27, p = 0.043), and cardiopulmonary dysfunction (elevated tricuspid jet velocity on echocardiogram, Hazard Ratio = 2.22, 1.23-4.02, p = 0.0082). Sixty-six percent of subjects were treated with hydroxyurea, although only 66% of those received a dose within the recommended therapeutic range. Hydroxyurea use was associated with improved survival (Hazard Ratio = 0.58, 95% CI 0.34-0.97, p = 0.040). This effect was most pronounced in those taking the recommended dose of 15-35 mg/kg/day (Hazard Ratio 0.36, 95% CI 0.17-0.73, p = 0.0050). Hydroxyurea use was not associated with changes in organ function over time. Further, subjects with higher fetal hemoglobin responses to hydroxyurea were more likely to survive (p = 0.0004). While alkaline phosphatase was lowest in patients with the best fetal hemoglobin response (95.4 versus 123.6, p = 0.0065 and 96.1 versus 113.6U/L, p = 0.041 at first and last visits, respectively), other markers of organ damage were not consistently improved over time in patients with the highest fetal hemoglobin levels. Our data suggest that adults should be treated with the maximum tolerated hydroxyurea dose, ideally before organ damage occurs. Prospective studies are indicated to validate these findings.